Ascorbic acid reduces redox potential in human spermatozoa subjected to heat‐induced oxidative stress. (1st March 2017) - Ahmad, G.; Agarwal, A.; Esteves, S. C.; Sharma, R.; Almasry, M.; Al‐Gonaim, A.; AlHayaza, G.; Singh, N.; Al Kattan, L.; Sannaa, W. M.; Sabanegh, E.
Summary: Oxidation–reduction potential (ORP) is a new measure of oxidative stress. It is a balance between the total available oxidants and reductants. This study measures the efficiency of ascorbic acid (AA) against oxidative stress induced by either heat alone or heat and hydrogen peroxide in sperm suspensions using the MiOXSYS System. Two concentrations of ascorbic acid (400 and 600 μmol/L) were tested against heat‐ and heat plus hydrogen peroxide‐induced oxidative stress in sperm suspensions after 2 and 4 hr of incubation. Sperm motility and static oxidation reduction potential (sORP) were measured at 2 and 4 hr of incubation at three different temperatures. A significant decrease in sORP was observed as a function of AA concentration. The 600 μmol/L AA had more pronounced reduction in sORP compared to 400 μmol/L AA ( p  = .001). Significant decreases in sperm motility ranging from 4.89% to 14.02% were observed both as a function of incubation time and addition of H2 O2 ( p  < .001). Ascorbic acid is efficacious to reduce heat‐induced oxidative stress in sperm preparations in vitro. The supplementation of ascorbic acid may be advantageous for semen preparations in IUI, IVF and ICSI.